y = 2x – 3 y = -x + 3 solve for x and y

Question

y = 2x – 3
y = -x + 3 solve for x and y

in progress 0
Helga 3 weeks 2021-08-27T06:36:02+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-27T06:37:17+00:00

    We are given the system of equations:

     \large{ \begin{cases} y = 2x - 3 \\ y =  - x + 3 \end{cases}}

    Since both are y-isolated equation, we can combine them together.

     \large{2x - 3 =  - x + 3}

    Isolate and solve for x-term.

     \large{2x - 3 + 3 + x =  - x + 3 + x  + 3} \\  \large{2x + x = 6 \longrightarrow  3x = 6} \\ \large{ \frac{3x}{3}  =  \frac{6}{3}  \longrightarrow  \boxed{ \red{x = 2}}}

    Next, we find the value of y. Simply substitute x = 2 in one of these equations. The less coefficient values, the faster and better. I will substitute x = 2 in y = -x+3. You can substitute x = 2 in y = 2x-3 if you want but the result would be the same.

     \large{y =  - x + 3}

    Substitute x = 2 in the equation.

     \large{y =  - 2 + 3} \\  \large \boxed{ \blue{y = 1}}

    Therefore – when x = 2, y = 1. We can write in coordinate point or ordered pair as (2,1) from (x,y).

    Answer

    • x = 2, y = 1
    • (2,1) — ordered pair

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )